IDENTIFICATION AND RESOLUTION OF ENGLISH PROBLEMS FOR KHOWAR LEARNERS IN PAKISTAN - Sami Ullah Khan; Nasir Abbas Syed; Munir Khan; Dolat Khan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study focuses on identification and resolution of problems of learning English in Pakistan. A group of ten undergraduate students of X University were sampled in this experiment, aimed at identifying the nature of errors in the speech of Pakistani students. They were asked to produce words of English in the forms of minimal pairs starting with English [v]-[w] consonants. The productions were recorded and analyzed acoustically in computer software using speech learning model (SLM) by James E Flege and colleagues. The results confirm that Pakistani students do not maintain the difference of lip-rounding between these two consonants of English. On the basis of the findings, this study recommends that English language teachers in Pakistan need to develop a phonetic realization of target consonants in the minds of adult English learners to enable them to acquire English as a second language.